A poluição atmosférica e o clima urbano: um olhar sobre a inspeção veicular no município de São Paulo - Santos, Andre Souza (2015)
This thesis of Master's Degree studies the air pollution in São Paulo as a result of automotive vehicles's predominance, taking as an example its influence on urban climate, comprising a period that started on the 1980s and is still in force. This analysis has as background the urbanization and the introduction of the automotive industry fomenting the use of collective and individual road s transports. Concerns about air quality and climate have turned the vehicles, once synonymous of economic progress and connected to a socio-economic identity,a worry for the urban environment and, as a solution, mechanisms to promote a road control were created. In the 1980s the guidelines were created for the control of automotive pollutants, in the 1990s, it was introduced Municipal rotation which has not produced the expected results in reducing emissions in the atmosphere,, then, only in 2008 was added the mandatory vehicle inspection in the city of São Paulo as a result of agreement between the countries that have ratified the Kyoto Protocol in1997 whose intention was to reduce between 2008 and 2012 greenhouse gas emissions in at least 5.2% compared to 1990s levels. According to the Intergovernmental Panel on Climate Change (IPCC) human action is the main responsible for the changes in air quality and climate and, if the countries achieve their goals, the pollution and global temperature could be reduced in between 1.4°C and 5.8°C until 2100.The study revealed that according to the urban development of St. Paulo in the field of displacements was prioritized road transport, this way, vehicular emissions of particulate materials in the atmosphere are connected to changes in the city climate and several health disorders,especially in winter when the polluted air disperses with difficulty although it is hard to quantify and qualify the real damage. As a result, there is the need to rethink the means of establishing shifts priorities for urban and environmental planning. In this case, the inspection car proved to be inefficient because, although the road contro it's hard, many vehicles without mechanical conditions remain in circulation mainlyin the suburbs directly influencing the data on air quality